Technical Efficiency and Intellectual Capital Islamic Banks in Indonesia - Hidayati, Irma; Nandiroh, Umi (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023)DO - 10.24843/JIAB.2023.v18.i02.p11, 2023)
This study explores the impact of intellectual capital on the technical efficiency of Islamic banks in Indonesia, emphasizing the shift from traditional physical assets to intellectual resources like digital systems, technologies, and brand value. It analyzes nine Islamic banks out of fourteen in Indonesia from 2013 to 2022 using a two-stage data analysis method. The first stage involves the Data Envelopment Analysis (DEA) model to measure technical efficiency, while the second stage uses the fractional regression model (FRM) instead of the traditional Ordinary Least Squares (OLS) method. The research introduces the iB-VAIC coefficient as a new intellectual capital metric. DEA results show that the average efficiency score for Indonesian Islamic banks is 0.945, with only two banks achieving a perfect score. The FRM analysis indicates a significant link between intellectual capital (iB-VAIC) and technical efficiency, with different components of intellectual capital having varied impacts. The study finds a negative correlation between bank size and technical efficiency and provides insights for bank management and policy development in Islamic banking. Keywords: data envelopment analysis, intellectual capital, technical efficiency